Strategies to Enhance Organizational Citizenship Behavior Among Educational Staff Through Strengthening Transformational Leadership, Emotional Intelligence, and Job Satisfaction - Aldilla Chandra, Khitara; Yusnita, Nancy; Sunaryo, Widodo (Amkop Management Accounting Review (AMAR), 2026)
This research is motivated by the suboptimal Organizational Citizenship Behavior (OCB) of private vocational high school education personnel in Bogor Regency, which is reflected in low work initiative, extra-role behavior, and participation in supporting organizational effectiveness. This study aims to analyze the direct and indirect effects of Transformational Leadership and Emotional Intelligence on OCB with Job Satisfaction as an intervening variable, as well as formulating strategies for improving OCB. The results show that Transformational Leadership has a direct positive and significant effect on OCB (β = 0.371), Emotional Intelligence has a direct positive and significant effect on OCB (β = 0.396), and Job Satisfaction has a direct positive and significant effect on OCB (β = 0.171). Transformational Leadership has a positive effect on Job Satisfaction (β = 0.127), and Emotional Intelligence has a positive effect on Job Satisfaction (β = 0.607). The indirect effects of Transformational Leadership and Emotional Intelligence on OCB through Job Satisfaction were β = 0.022 and β = 0.103, respectively. These findings indicate that strengthening transformational leadership, developing emotional intelligence, and increasing job satisfaction are important strategies for improving OCB.